Governing climate change : global cities and transnational lawmaking / Jolene Lin. - Lin, Jolene (Cambridge studies on environment, energy and natural resources governance, 2018)
Cities are no longer just places to live in. They are significant actors on the global stage, and nowhere is this trend more prominent than in the world of transnational climate change governance (TCCG). Through transnational networks that form links between cities, states, international organizations, corporations, and civil society, cities are developing and implementing norms, practices, and voluntary standards across national boundaries. In introducing cities as transnational lawmakers, Jolene Lin provides an exciting new perspective on climate change law and policy, offering novel insights about the reconfiguration of the state and the nature of international lawmaking as the involvement of cities in TCCG blurs the public/private divide and the traditional strictures of 'domestic' versus 'international'. This illuminating book should be read by anyone interested in understanding how cities - in many cases, more than the countries in which they're located - are addressing the causes and consequences of climate change.